Sodium cobalt(II) tetrasulfophthalocyanine and catalytic oxidation of ethanethiol - Scott, Dane W.; Myers, Dwight L.; Hill, Hannah; Omadoko, Ovuokenye (Fuel (Guildford), 2019)
[Display omitted] The oxidation of thiols in petroleum is a subject of ongoing research, discussion and removal of sulfur is a topic of ongoing legislation. The Merox® process requires high pressures and temperatures. Novel catalysts and methods innovations are of interest. This work examines the synthesis, purification and use of sodium cobalt(II) tetrasulfophthalocyanine to oxidize ethanethiol to diethyl disulfide. Many systems using phthalocyanines carry out the oxidation reaction under basic conditions. This work oxidized ethanethiol to diethyl disulfide in dimethylformamide using cobalt tetrasulfophthalocyanine (CoTSPc) under alkali free conditions and was compared to cobalt sulfate heptahydrate, cobalt phthalocyanine (CoPc), FeTSPc and CuTSPc. The reaction was carried out in oxygen saturated DMF while stirring at 15, 25 and 40.00 °C. The amount of ethanethiol remaining over time was determined using Ellman’s reagent. A simple GC method quantified the amount of diethyl disulfide. The reaction proceeded to completion within 10 min at 40.00 °C. A turn over number of 72 and frequency of 8.1 min−1 is obtained. The activation energy was approximately 32 kJ/mol. The prepared CoTSPc catalyst was most catalytic toward oxidation of ethanethiol followed by cobalt sulfate heptahydrate, CoPc, FeTSPc and CuTSPc was non-catalytic.